LAMA WAKTU FERMENTASI TERHADAP SIFAT FISIKO˗KIMIA TEH KOMBUCHA DARI DAUN KELOR - Fadillah Zahra; Noviar Harun; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
A popular product made from Moringa leaves is tea. Infusion of Moringa leaves will have more nutrition if it is fermented into kombucha, because kombucha drinks have high antioxidant activity when compared to drinks that have not been made kombucha. This study aims to determine the optimal length of fermentation time for the physicochemical properties of kombucha tea produced from Moringa leaf. The study used a completely randomized design with five treatments and 4 replications. In this study, kombucha tea was made with variations in the length of fermentation, time namely L1 (6 days fermentation), L2 (7 days fermentation), L3 (8 days fermentation), L4 (9 days fermentation) and L5 (fermentation time 10 days). The parameters observed included the degree of acidity (pH), vitamin C, antioxidant activity and overall hedonic test. The treatment chosen was L1 (6 days fermentation time) with a value of 3.29 degrees of acidity, 22.88 mg/100ml of vitamin C, antioxidant activity with an IC50 value of 1.25 g/ml and an overall hedonic test of 2.75 (somewhat like ). Keywords: fermentation time, kombucha tea, moringa leaf